Phenotypic Trait Variation in Populations of a Global Invader Mayweed Chamomile (Anthemis cotula): Implications for Weed Management - Adhikari, Subodh; Burke, Ian C.; Piaskowski, Julia; Eigenbrode, Sanford D. (Frontiers in Agronomy, 2021)
Mayweed chamomile (Anthemis cotula L.) is an annual crop weed that has become a substantial impediment to diversify traditional wheat-based cropping systems such as in the Pacific Northwest (PNW), USA. Some of the broadleaf rotational crops are vulnerable to the weed as they are less competitive or lack compatible herbicides for A. cotula management. Although A. cotula has been present in the PNW for more than a century, traits that contribute to invasiveness and how these vary among the weed populations have not been investigated. We assessed trait variation with a common garden greenhouse experiment by comparing 19 A. cotula populations from the PNW and Kashmir Valley, India. Seeds from individual plants from each population were used to grow plants through their senescence. We measured phenological (e.g., flowering duration), morphological (e.g., plant biomass), reproductive fitness (e.g., number of flower heads), and physiological (floral scent VOCs: volatile organic compounds) traits on individual plants and analyzed the data using mixed-effects models. We found high inter-population variation in most of the traits measured, but the variation was not associated with the geographical distance. Seedling emergence within 30 days of planting ranged from 2 to 49 % for PNW populations to 55 to 72 % for Indian populations. Flowering duration ranged from 2 to 3 months among populations. Other traits such as initial and final flowering dates, the total number of flower heads, and floral scent VOCs also differed among populations. These trait patterns may indicate a localized adaptation of A. cotula populations to environmental or management regimes, variation arising from anthropogenic or natural dispersal, multiple introductions, genetic drift, or combinations of these. Regardless of the processes, the trait variation suggests that weed management plan for A. cotula may need to be tailored to specific locations instead of a uniformly adopted plan across the region.